Nursing and hospitalized high-risk pregnant women: challenges for comprehensive care - Bruna Felisberto de Souza; Jamile Claro de Castro Bussadori; José Ricardo de Carvalho Mesquita Ayres; Márcia Regina Cangiani Fabbro; Monika Wernet (SciELO, 2020)
Abstract Objective: To analyze the interactions between nursing and hospitalized high-risk pregnant women regarding the possibilities and limits of providing care guided by the principle of comprehensiveness. Method: A qualitative study based on the conceptual framework of comprehensiveness and developed from the precepts of thematic content analysis. Data were collected through open interviews and observation of the care scenario of twelve nursing professionals with hospitalized high-risk pregnant women. Results: Twelve (12) nursing professionals participated in the study. Nursing practices are portrayed from two thematic categories: "Embracement: emotional and informational support" and "Assessing and monitoring gestational risk". The findings revealed intentions to embrace women, providing informal and emotional support, but under weaknesses in intersubjective relationships. There is an emphasis on "technical success", not always sufficiently articulated with "practical success" in care actions, with harm to achieving comprehensiveness. Conclusion: The findings revealed that an emphasis on the biomedical management of obstetric risk and structural and organizational limitations of work end up hindering incorporating into daily care the concerns and knowledge necessary for constructing its comprehensiveness.